Wikis as digital learning resources in nursing education - Kjersti Røsvik; Thor Arne Haukedal (Nordic Journal of Digital Literacy, 2017)
Abstract This article examined how first year undergraduate nursing students experienced the use of wikis as pedagogical learning resources in a social science module. The purpose of the study was to investigate how wikis contributed to collaboration and academic interests, using following question: How do students evaluate the use of wiki-based learning in a social science learning module? Are there possible patterns in the covariance between the questions that concern the evaluation of wiki-based learning? Are there any differences in respondents’ ages related to the evaluation of wiki-based learning? The method used was a cross-sectional study. The sample consisted of all students attending classes in spring 2013.